(untitled) (Universal International Scientific Journal, 2026)
Globalization processes impose new and complex tasks on managers in the modern management system. In such conditions, not only the professional knowledge and skills of managers, but also their emotional intelligence are of great importance. Emotional intelligence represents the ability of a manager to understand his own emotions, manage them, correctly perceive the emotions of others, and form effective social relationships. The process of developing the emotional intelligence of managers in the context of globalization and its relationship with mental health are scientifically and theoretically analyzed. The role of managers in the formation of emotional stability, stress resistance, and a healthy psychological environment is also highlighted.